Medan Makna Aktifitas Mulut dalam Bahasa Sasak Dialek Meno-Meni Desa Sakra, Lombok Timur - Lalu Purnama Zulkarnaen; Sri Sukarni (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
This study describes the types of meaning fields of oral activity lexemes found in the expression of the Sasak language in Sakra Village, East Lombok Regency, Meno-Meni dialect. The theory used in this study is the semantic theory that describes the form and components of meaning it contains. The population in this study is the language-using area in Sakra Village, Sakra District. Data collection used a random sampling technique (random sample selection) with informant selection criteria. The data collection method was carried out by the listening method with the tapping technique and the listening technique involving conversation and note-taking. The use of these methods was adjusted to the research field. In data analysis, a qualitative descriptive study was used that had intralingual and extralingual equivalent methods. The presentation of the results of data analysis in this study used formal and informal methods. Based on the results of data analysis, in the Sasak language of Sakra Village, East Lombok, Meno-Meni dialect used to express oral activity, namely the oral activity lexeme of the Sasak language of the Meno-Meni dialect of Sakra Village amounted to 27 lexemes. These lexemes are classified into oral activities based on their function, thus creating five subfields of meaning from four oral activities: the oral activity of eating, which has eight lexemes: delat, mangan, emet, anget, kritik pecak, nyak-nyak, and kaken; the oral activity of drinking, which has two lexemes: begeleg and serut; the oral activity of speaking, which has twelve lexemes: nyemperaq, bekoeh, peseq, becerite, bewaran, ngeraos, muni, tomes, rancik, bejelemetn, gerumun, and nyempate; the oral activity of smoking, which has one lexeme: ngudut; and the oral activity of vocalizing, which has two lexemes: meok and besuit.